δ13C results of bulk organic matter in marine surface sediments from the Laptev Sea, Arctic Ocean - Tsai-Wen Lin; Hanno Meyer; Tommaso Tesi; Mikaela Weiner; Andreas Marent; Alessio Nogarotto; Gesine Mollenhauer (PANGAEA, 2025)
The data were obtained from marine surface sediments (0-1 cm depth) from the Laptev Sea during three research expeditions. Samples were retrieved using box corers and multiple corers, and the sediments were dried immediately after subsampling. Sample pretreatment and measurements were carried out at the AWI ISOLAB Facility - Stable Isotope Laboratory Potsdam (see https://registry.o2a-data.de/items/7986) and CNR-ISP in Bologna. For samples analyzed at the ISOLAB Facility, samples were ground, acidified with 6 M HCl at 60 °C for three hours and dried before sending to the ISOLAB Facility. At the ISOLAB Facility, acidified samples were homogenized and weighed into tin capsules. The amount of sample used for δ13C analysis was based on TOC content, aiming for 0.2 mg of organic carbon per measurement. Analyses were performed using a Thermo Fisher Scientific Delta-V-Advantage gas mass spectrometer coupled with a FLASH elemental analyzer EA 2000 and a CONFLO IV gas mixing system (see https://registry.o2a-data.de/items/7984). At CNR-ISP, approximately 15 mg of sediment was weighed into silver boats, acidified with 1.5 M HCl, and dried at 55 C. The samples were analyzed using a Thermo Fisher Scientific DeltaQ IRMS coupled with a FLASH 2000 CHNS Analyzer via a CONFLO IV gas mixing system. The standard deviation (1σ) of δ13C measurement was generally better ±0.15 extperthousand for the ISOLAB Facility, and better than ±0.1 extperthousand in CNR-ISP.
In: Lin, Tsai-Wen; Nehrke, Gernot; Mollenhauer, Gesine (2025): Bulk organic matter data of Lena Delta permafrost, marine surface sediment, and sediment cores from the Laptev Sea, Arctic Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984732